Risk in Sports and Challenges for Sports Organizations - Winner, Hannes; Barth, Michael; Schnitzer, Martin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Success, injuries, future career opportunities of athletes, and the societal gains of participating in sports and organizing (mega) sports events are all related to individual risk-taking behavior. Although the sports economics and management literature has broadly addressed these issues, it is surprising that less attention has been paid to the implications of risk-taking on the organization of sports in general and, more particularly, on the design and behavior of sports organization members.